Children's health, human capital accumulation, and R&D-based economic growth - Annarita Baldanzi; Alberto Bucci; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyze the effects of children's health on human capital accumulation and on long-run economic growth. For this purpose we design an R&D-based growth model in which the stock of human capital of the next generation is determined by parental education and health investments. We show that i) there is a complementarity between education and health: if parents want to have better educated children, they also raise health investments and vice versa; ii) parental health investments exert an unambiguously positive effect on long-run economic growth, iii) faster population growth reduces long-run economic growth. These results are consistent with the empirical evidence for modern economies in the twentieth century.
urn:nbn:de:bsz:100-opus-13290
Keywords: I15; I25; J10; O30; O41; 330; Children's Health; Education; Fertility; Economic Growth; Technological Progress; Long-run Economic Development